A surface‐based technique for mapping homotopic interhemispheric connectivity: Development, characterization, and clinical application. Issue 8 (24th May 2016) - Tobyne, Sean M.; Boratyn, Daria; Johnson, Jessica A.; Greve, Douglas N.; Mainero, Caterina; Klawiter, Eric C.
Abstract: The functional organization of the human brain consists of a high degree of connectivity between interhemispheric homologous regions. The degree of homotopic organization is known to vary across the cortex and homotopic connectivity is high in regions that share cross‐hemisphere structural connections or are activated by common input streams (e.g., the visual system). Damage to one or both regions, as well as damage to the connections between homotopic regions, could disrupt this functional organization. Here were introduce and test a computationally efficient technique, surface‐based homotopic interhermispheric connectivity (sHIC), that leverages surface‐based registration and processing techniques in an attempt to improve the spatial specificity and accuracy of cortical interhemispheric connectivity estimated with resting state functional connectivity. This technique is shown to be reliable both within and across subjects. sHIC is also characterized in a dataset of nearly 1000 subjects. We confirm previous results showing increased interhemispheric connectivity in primary sensory regions, and reveal a novel rostro‐caudal functionally defined network level pattern of sHIC across the brain. In addition, we demonstrate a structural–functional relationship between sHIC and atrophy of the corpus callosum in multiple sclerosis ( r  = 0.2979, p  = 0.0461). sHIC presents as a sensitive and reliable measure of cortical homotopy that may prove useful as a biomarker in neurologic disease. Hum Brain Mapp 37:2849–2868, 2016 . ©2016 Wiley Periodicals, Inc.